The Description of the Siege of Székesfehérvár by Wolfgang Lazius.: A Hidden Oratio Funebris in a Historical Work - Bránya, Krisztina (Sapiens ubique civis, 2023)
The siege of Székesfehérvár in 1543 that lead to the city’s one-century-long Turkish occupation was narrated by Johannes Martinus Stella (an Italian soldier), Miklós Istvánffy (the most famous Hungarian historian of the 16th century), and György Szerémi (a Hungarian priest working under János Szapolyai). The former two mainly focused on the events of the siege, while the latter used the 15th century’s religious conflict as a focus point. A common point in all of their works is that they all briefly mention György Varkocs, the captain of Székesfehérvár. On the contrary, the historian of Ferdinand I, Wolfgang Lazius devotes the part dealing with the siege of Székesfehérvár in his monumental historical work to writing an obituary to György Varkocs. In my presentation I show how did Wolfgang Lazius use the siege’s events that were appropriately narrated by the aforementioned authors, to hide a well-written oratio funebris of György Varkocs in the historical description of the siege of Székesfehérvár.